2023
DOI: 10.3389/fneur.2023.1098141
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid to serum creatinine ratio predicts neurological deterioration in branch atheromatous disease

Abstract: Background and objectiveBranch atheromatous disease (BAD) makes patients prone to early neurological deterioration (END), resulting in poor prognosis. The aim of this study was to investigate the association between SUA/SCr and END in BAD stroke patients.MethodsWe conducted a retrospective study that included 241 patients with BAD-stroke within 48 h of symptom onset. We divided the patients into the END group and the no END group. END was defined as an NIHSS score increase of more than 2 points within 1 week. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A large‐scale registry study revealed a significant link between a lower SUA/SCr ratio and poor functional outcome in AIS [16]. It has been reported that, in patients with lenticulostriate artery infarcts, a lower SUA/SCr ratio was an independent predictor of early neurological deterioration, leading to an unfavourable prognosis [17]. Additionally, one study highlighted a positive correlation between SUA/SCr ratio and the stroke recurrence risk in young adults experiencing ischaemic stroke [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large‐scale registry study revealed a significant link between a lower SUA/SCr ratio and poor functional outcome in AIS [16]. It has been reported that, in patients with lenticulostriate artery infarcts, a lower SUA/SCr ratio was an independent predictor of early neurological deterioration, leading to an unfavourable prognosis [17]. Additionally, one study highlighted a positive correlation between SUA/SCr ratio and the stroke recurrence risk in young adults experiencing ischaemic stroke [18].…”
Section: Discussionmentioning
confidence: 99%
“…At admission, their baseline NIHSS score was 15 (11)(12)(13)(14)(15)(16)(17)(18)(19). A total of 148 (20.2%) patients received intravenous thrombolytic therapy.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, assessing the relationship between SUA/SCR and cognitive impairment necessitates considering the influence of renal function. Research has found that SUA/SCR serves as a high-quality biomarker reflecting endogenous UA levels 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%